An ionic/thermal-responsive agar/alginate wet-spun microfiber-shaped hydrogel combined with grooved/wrinkled surface patterns and multi-functions. (15th March 2023) - Wan, Yekai; Liu, Haoran; Yan, Kun; Li, Xiufang; Lu, Zhentan; Wang, Dong
Abstract: A dual stimuli-responsive wet-spun microfiber-shaped hydrogel is prepared by injecting a hot blend of two stimuli biopolymers alginate (i.e., ionic-responsive) and agar (i.e., temperature-responsive) into a pre-cooling and metal cation containing coagulation bath. Experimental results indicate the fiber microstructure could be manipulated by the extrusion rate and cooling temperature, achieving an anisotropic shrinkage characteristic and novel grooved/wrinkled surface patterns. Importantly, the integration of metal cations (e.g., Ca 2+ and/or Zn 2+ ) was confirmed to significantly improve the hydrogel mechanical properties (i.e., double networks) and enhanced blue fluorescent intensity as a typical metal-polymer complexation formed within the agar gel matrix. Moreover, the functionality-independent double networks enabled typical pH-shape memory and sustainable antibacterial properties have also been demonstrated. Therefore, combing the facile fabricating approach and multifunctionality, this study would advance the development of stimuli-responsive hydrogel microfiber for complex biomedical systems. Graphical abstract: Unlabelled Image